Differences in quality of life among college student electronic cigarette users - Ridner, S. Lee (AIMS Public Health, 2018)
PURPOSE: The purpose of this study was to explore an association between e-cigarette use and Quality of Life (QOL) among college students. METHODS: During February 2016, 1,132 students completed an online survey that included measures of tobacco use and the WHOQOL-BREF instrument. Differences were tested using Chi-square, Fisher's exact test, and ANOVA, and regression was used to assess possible relationships. RESULTS: E-cigarettes were used by 6.97% of the participants, either solo or along with traditional cigarettes. Bivariate analyses suggest that male college students are more likely than females to use e-cigarettes, either solo or in combination with traditional cigarettes (χ(2) =19.4, P < .01). Lesbian, gay, and bisexual students are more likely than heterosexual students to use traditional cigarettes, either solo or in combination with e-cigarettes (χ(2) = 32.9, P < .01). Multivariate models suggest that for every 10-unit increase in overall QOL, psychological well-being, social relations or environmental health the adjusted odds of being a sole cigarette user were significantly lower (all, P < .01), respectively. For every 10-unit increase in psychological well-being the adjusted odds of being a dual user was significantly lower (OR = .83, P = .026). CONCLUSIONS: Findings indicate that lower quality of life appears to be connected to tobacco use.